2014
DOI: 10.2459/jcm.0000000000000040
|View full text |Cite
|
Sign up to set email alerts
|

Positive trend in survival to hospital discharge after out-of-hospital cardiac arrest

Abstract: Survival to hospital discharge after OHCA has significantly improved. Many aspects may influence survival, but surely, the reduction of time and an early and good quality CPR have positively influenced the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 57 publications
0
16
0
Order By: Relevance
“…Survival in out-of-hospital cardiac arrest ranges from 4.3% to 10.7% [1][2][3][4][5]. Effective chest compressions are the mainstay of cardiopulmonary resuscitation (CPR) and increase the likelihood of surviving cardiac arrest [6][7][8][9][10]. Proper hand position, and appropriate rate and depth of compressions are among the most important parameters during chest compressions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Survival in out-of-hospital cardiac arrest ranges from 4.3% to 10.7% [1][2][3][4][5]. Effective chest compressions are the mainstay of cardiopulmonary resuscitation (CPR) and increase the likelihood of surviving cardiac arrest [6][7][8][9][10]. Proper hand position, and appropriate rate and depth of compressions are among the most important parameters during chest compressions [11].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, the survival outcomes for out-of-hospital cardiac arrest in both children and adults have been quite poor, though it is improving. 1 Similarly, the incidence of lay rescuer community cardiopulmonary resuscitation has been quite low with previous estimates of 10-15% 2 , though recent estimates show some improvementalthough still poorin the 30% range. 3 Several studies in the last several years have suggested that lay rescuer community cardiopulmonary resuscitation/ambulatory external defibrillation use can be increased by community education initiatives, and a concomitant increase in out-of-hospital cardiac arrest survival can be expected.…”
mentioning
confidence: 80%
“…In Italy the incidence of out of hospital cardiac arrest (OHCA) is estimated to be 1 case over 1000 people per year [2] and the survival is actually low. A quantitative review of the literature by our group [3] showed that survival to hospital discharge has increased worldwide over the years but it is still low amounting to about 10%. It has been widely demonstrated that the survival of cardiac arrest patients depends on early and good quality cardio-pulmonary resuscitation (CPR) and defibrillation, on the time of intervention and on the post-cardiac arrest care.…”
Section: To the Editormentioning
confidence: 98%